2000
DOI: 10.1177/014920630002600505
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical and Empirical Analysis of Journal Rankings: The Case of Formal Lists

Abstract: This study examines the use of formal rankings of journals by management departments for personnel decision purposes. We posit that the probability of adopting a list of formal rankings is related to a set of characteristics of the department. Few schools have formal lists of journals. Our empirical findings imply that the probability of adopting a list is positively correlated with department size and is inversely correlated with the perceived quality of the department. Considerable variation exists across su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 47 publications
5
81
0
Order By: Relevance
“…In addition, the study helps identify whether regional differences exist in relation to publication preference. Prior research has observed that the elite of the academic profession, who may not represent the total academic population, created most of the other ranking indices (Theoharakis and Hirst, 2002;Van Fleet et al, 2000). By taking into consideration views from a wide spectrum of academics, this study provides a much more balanced view related to academic journal rankings.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the study helps identify whether regional differences exist in relation to publication preference. Prior research has observed that the elite of the academic profession, who may not represent the total academic population, created most of the other ranking indices (Theoharakis and Hirst, 2002;Van Fleet et al, 2000). By taking into consideration views from a wide spectrum of academics, this study provides a much more balanced view related to academic journal rankings.…”
Section: Introductionmentioning
confidence: 94%
“…The tendency also exits to grant a higher grade to journals in which a person him-or herself has published (see Extejt and Smith, 1990;Jobber and Simpson, 1988;Todorov and Glanzel, 1988). Van Fleet et al, (2000) claim that if a panel comprises professors and senior academics that have considerable top journal publications, new and upcoming journals are disadvantaged from developing into quality journals because they are ignored. This disadvantageous positioning may then extend to academics who publish in such journals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evaluation of a journal's quality is far from simple, and both the journals included in various MOS lists and their attendant quality ratings are highly variable and hotly contested (Lewis, 2008;Van Fleet, McWilliams & Siegel, 2000). Moreover, currently, there are no theoretical frameworks that account for the variable perceptions of journal quality that appear to be at least partly responsible for the lack of consensus surrounding journal lists.…”
Section: (204 Words)mentioning
confidence: 99%
“…To address this question, we conducted a content analysis of 300 management articles. We began by defining our sampling frame from well-accepted lists of top management journals (e.g., Short, Payne, & Ketchen, 2008;Van Fleet, McWilliams, & Siegel, 2000;Werner, 2002). From these lists, we maintained one to two specialty journals per subdomain and only those journals that publish theoretical and/or empirical pieces.…”
Section: Content Analysismentioning
confidence: 99%